Criopreservação do sêmen de pirapitinga Piaractus brachypomus (PISCES, CHARACIDAE) - Medina, Sandra Piedad Velásquez (2008)
The pirapitinga (Piaractus brachypomus ) is a species of exotic fish introduced in the Brazilian north-eastern, with great commercial importance for its alimentary habit, excellent growth, handling resistance in captivity and against diseases. The cryopreservation of its semen can contribute in the economic, genetic and environment aspects of the region and the species. The objective of this work was to develop an adequate protocol of seminal frozen to be able to obtain motility closer to the fresh semen. It was worked with the semen of 19 mature males between December of 2007 and March of 2008, determining its seminal characteristics; the cryoprotectants toxicity DMSO 10% and methylglicol 10%, diluted in glucose 5%, ACP-104 and Ringer solution at 1:3, 1:5 and 1:7 dilutions, during 15 minutes at 4°C; the cryopreservation at -196°C with the same cryoextenders using 0,25 and 0,5 mL straws, frozen in nitrogen vapor inside styrofoam boxes or in dry shipper, being later transferred to cryogenic containers for 15 days. It was evaluated the motilities and speeds through the computer-assisted sperm analysis (CASA) post-thawed; and the morphology in fresh and post-thawed semen. The seminal parameters observed in fresh semen were: objective mean motility of 94%, concentration of 44 x 109 spzt/mL, semen volume of 7 mL, osmolarity of 317 mOsm/kg and pH of 8,4. In the toxicity tests weren’t find significant differences between T3 (Ringer+Methylglicol 10%) at 1:3 dilution compared with the control group (P=0.06), showing motility of 80% and VCL of 95 μm/s. The best frozen method was in dry shipper using 0.5 mL straws, registering motility of 62% for T6 (Glucose+DMSO 10%) at 1:7 dilution, however, showing low speeds for all treatments, with better results of VCL, VSL and VAP to T6. In fresh semen, the morpho anomalies most found was the tail doubled (20%) and in the post-thawed semen, the tail coiled (23%). Comparing the morpho anomalies results before and after frozen it was observed significant differences between samples (P<0.05). It was concluded that the pirapitinga semen can be preserved in Ringer+Methylglicol 10% in 1:3, without presenting high toxicities, and cryopreservated in Glucose+DMSO 10% using dry shipp.